EVALUATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTs) TOOLS CONTRIBUTING TO RURAL DEVELOPMENT - Modiba F.S.; Kaye S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The move towards embracing the fourth industrial revolution by the South African government to explore more employment opportunities brings questions on how rural communities will be supported to join this digital revolution. However, measurement tools for ICTs in rural areas could be more varied. Furthermore, existing measurement tools are designed for organisations, thus excluding the individuals who are at the receiving end of development, thus extending the digital divide. This paper explores how rural development can be measured, focusing on individuals and communities. A qualitative semi-integrative review was conducted, and data was analysed using content analysis. Results revealed that specific measurement tools for measuring the impact of ICTs in rural development are limited, and only a few frameworks could be identified, suggesting a need for more inclusive approaches. Available frameworks are project-focused and do not allow self-evaluations by community users experiencing other ICTs. Additionally, it was revealed that while a focused measurement tool is required, CA and including relevant livelihood assets can be valuable for evaluating ICT impact. A framework was proposed that could be feasible for South African rural communities. The implication for practice is that infrastructural challenges are at the heart of the digital divide; therefore, policymakers and development practitioners should push for policies promoting digital inclusion and readiness in rural areas.